2015
DOI: 10.1128/iai.03109-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Two-Component Regulatory System, HptRS, the Regulator for the Hexose Phosphate Transport System in Staphylococcus aureus

Abstract: e Hexose phosphate is an important carbon source within the cytoplasm of host cells. Bacterial pathogens that invade, survive, and multiply within various host epithelial cells exploit hexose phosphates from the host cytoplasm through the hexose phosphate transport (HPT) system to gain energy and synthesize cellular components. In Escherichia coli, the HPT system consists of a two-component regulatory system (UhpAB) and a phosphate sensor protein (UhpC) that tightly regulate expression of a hexose phosphate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 49 publications
0
43
0
6
Order By: Relevance
“…The increased levels of GlpK and GlpD might reflect the utilization of glycerol, which is known as one of the preferred carbon sources during intracellular growth of other pathogens such as Listeria monocytogenes 26 . For S. aureus , previous studies reported upregulation of the uhpT gene encoding a hexose phosphate transporter upon internalization 23 , 27 , 28 . Enzymes of the TCA cycle increased in level in S. aureus following internalization as already observed by Surmann et al .…”
Section: Resultsmentioning
confidence: 97%
“…The increased levels of GlpK and GlpD might reflect the utilization of glycerol, which is known as one of the preferred carbon sources during intracellular growth of other pathogens such as Listeria monocytogenes 26 . For S. aureus , previous studies reported upregulation of the uhpT gene encoding a hexose phosphate transporter upon internalization 23 , 27 , 28 . Enzymes of the TCA cycle increased in level in S. aureus following internalization as already observed by Surmann et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, transposon mutants of the two membrane‐anchored glycerophosphodiesterases showed no growth defect in SNM3‐Glu when GroPC was the sole carbon source (data not shown), suggesting that the secreted GlpQ is a major enzyme for the cleavage of GPDs. Transporters for Gro‐3P have been described in S. aureus , GlpT, and UgpT, (Park et al ., ), which may accomplish the uptake of Gro‐3P upon GlpQ‐mediated release from GPDs. GroPC transporters have been described in other bacteria and the potential existence of such a transporter in S. aureus might enable the use of GroPC in SNM3‐Glu media to some degree, even when GlpQ is not present.…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall synthesis inhibitor fosfomycin is currently used in the treatment of urinary tract and gastrointestinal S. aureus infections. Fosfomycin can enter the cell via the L-α-glycerophosphate transport system and/or the hexose-monophosphate transport system (UhpT) [89]. Mutations in these transporters contribute to fosfomycin resistance and are presumably a major mechanism of fosfomycin resistance [90].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%